Evaluating the dynamics of fee-free higher education in South Africa: a causal loop diagram approach [version 3; peer review: 2 approved, 1 not approved] - Grace Kanakana-Katumba; Tlotlo Ramasu (F1000Research)
Background This research investigated the dynamics of fee-free higher education in South Africa, analysing the interplay of socioeconomic, political, and institutional factors to elucidate the complexities surrounding its implementation and impact. Using a causal loop diagram approach (CLD), the study aims to identify key factors to effective implementation, how they interact to shape the outcome of the policy, and actionable strategies to address the challenges hindering the policy sustainability. Method A participatory approach was used to developing the CLD, integrating insights from an extensive literature review and stakeholder opinion. The initial CLD was constructed based on evidence from prior research contextualizing fee-free higher education within South Africa’s unique socio-political sector. Discussions with stakeholders and experts provided critical feedback to refine the model, ensuring its relevance and accuracy. The CLD methodology was selected for its ability to illustrate complex interdependencies and systemic challenges. Results Key findings highlight the impact of funding constraints, which create reinforcing feedback loops limiting access and infrastructure improvements. Also, administrative inefficiencies within the National Student Financial Aid Scheme (NSFAS) result in delays and inconsistencies, reducing policy inclusivity, and decentralized implementation across institutions perpetuates disparities in quality and access. Conclusion The study concludes the urgent need for systemic reforms, including digitising financial aid processes, centralising NSFAS operations, and improving resource allocation to under-resourced institutions. Furthermore, the study aligns with global goals, particularly Sustainable Development Goals (SDGs) 4 (Quality Education), 8 (Decent Work and Economic Growth), and 10 (Reduced Inequalities), as well as the African Agenda 2063’s focus on human capital development. While the findings offer valuable recommendations for policymakers, further research is needed to explore longitudinal impacts of these reforms and expand comparative analyses with other nations implementing similar policies.